(untitled) (Research, Society and Development, 2021)
The growth of cities, along with the disorderly formation of large metropolises around the world, results in major changes in Land Use. However, few studies relate the urban sprawl and its effects on the cities of the Northeast of Brazil (NEB). Thus, this study aimed to evaluate the urban sprawl in Maceió-Alagoas between 1985 to 2020 from orbital Land Surface Temperature (LST) and Normalized Difference Vegetation Index (NDVI) products to detect the changes and their environmental effects. This study used orbital products acquired from the systems-sensors Landsat 5 / Thematic Mapper (TM) and 8 / Operational Land Imager (OLI). The study used four images to observe the Spatio-temporal variation of urbanization, corresponding to the years 1987, 1998, 2006, and 2020. It used the environment software R for the generation of NDVI and LST thematic maps. The results obtained pointed out substantial changes in the Land Use detected by the NDVI and increased LST over the 35 years. Such variability occurred in the neighborhoods located in the northern and northwestern portion of the city, resulting from the incentive programs of the Federal Government in 2010, mainly the Benedito Bentes Complex (CBB), with the most significant transformations in the use and occupation of the soil, mainly the largest increase in LST between 7.5-10.0 °C. The effects produced by urban sprawls have been mitigated due to the environmental protection areas.